2013
DOI: 10.1038/srep02658
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative full time course analysis of nonlinear enzyme cycling kinetics

Abstract: Enzyme inhibition due to the reversible binding of reaction products is common and underlies the origins of negative feedback inhibition in many metabolic and signaling pathways. Product inhibition generates non-linearity in steady-state time courses of enzyme activity, which limits the utility of well-established enzymology approaches developed under the assumption of irreversible product release. For more than a century, numerous attempts to find a mathematical solution for analysis of kinetic time courses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…5). These results can be interpreted in terms of product inhibition and/or substrate depletion, mimicking what has been observed for enzymatic reactions [26,27]. The initial velocity decreases as the pH of the incubation medium increases.…”
Section: Selection Of the Operational Parameterssupporting
confidence: 56%
See 2 more Smart Citations
“…5). These results can be interpreted in terms of product inhibition and/or substrate depletion, mimicking what has been observed for enzymatic reactions [26,27]. The initial velocity decreases as the pH of the incubation medium increases.…”
Section: Selection Of the Operational Parameterssupporting
confidence: 56%
“…Using this approach, we have observed that the relaxation rate constant decreases with 5-HIAA concentration, suggesting that substrate depletion may account for non-linearity in the kinetic data [26]. The substrate concentration-dependence of the initial velocities obtained from fitting data to Eq.…”
Section: Selection Of the Operational Parametersmentioning
confidence: 98%
See 1 more Smart Citation
“…Time courses were fit to the nonlinear function [P] = v 0 /h(1 À e Àht ), where P is the product, v 0 is the initial velocity, and h is the relaxation constant of v 0 that describes nonlinearity in progress curves (Cao and De La Cruz, 2013). Initial velocities were plotted against UDP-glucose concentrations and fit to the Michaelis-Menten equation v = V max [S]/K m + [S], to determine the kinetic constants K m and V max for each concentration of phloretin.…”
Section: Kinetic Measurementsmentioning
confidence: 99%
“…Extraneous inhibitors present in unpurified enzyme solutions or in cell extracts systematically affect the quality of kinetic measurements [6]. Product inhibition can usually be ignored in initial-rate measurements but is highly misleading in time-course studies [7]. Compound aggregation can cause enzyme sequestration on the surface of the aggregate particles and is one of the main reasons for promiscuous enzyme inhibition [3].…”
Section: Introductionmentioning
confidence: 99%